Physical Fitness Differences Between Prepubescent Boys and Girls - Marta, Carlos C. (2020)
The purpose of this study was to analyze in which physical capabilities boys and girls are closer or distant. An additional objective was to find which of the body fat, physical activity, and somatotype factors have a greater effect on prepubescent children's physical fitness. This was a cross-sectional study involving 312 children (10.8 ± 0.4 years). The physical fitness assessment employed sets of aerobic fitness, strength, flexibility, speed, agility, and balance. The boys presented higher values in all selected tests, except tests of balance and flexibility, in which girls scored better. Gender differences in the physical fitness were greatest in the explosive strength of upper (p ≤ 0.01, η(p)(2) = 0.09) and lower limbs (p ≤ 0.01, η(p)(2) = 0.08), although with a medium-size effect of gender, and smaller in the abdominal (p > 0.05, η(p)(2) = 0.007) and upper limbs (p > 0.05, η(p)(2) = 0.003) muscular endurance, and trunk extensor strength and flexibility (p > 0.05, η(p)(2) = 0.001). The endomorphic (p ≤ 0.01, η(p)(2) = 0.26) in the girls, and the ectomorphic (p ≤ 0.01, η(p)(2) = 0.31) and mesomorphic (p ≤ 0.01, η(p)(2) = 0.26) in the boys, had the high-sized effect on the physical fitness. The physical activity in the girls, and the endomorphic and body fat in the boys, did not have a significant effect. These findings can help in the planning of activities that take into account the success and motivation of both boys and girls and thus increase levels of physical activity and physical fitness at school. However, in prepubescent children, one cannot neglect the influence of genetic determinism, observed from the morphoconstitutional point of view.